Eliciting Activity Goals With a Self-Administered Survey Among Patients With Hip or Knee Osteoarthritis. Issue 4 (November 2022) - Alan Fontana, Mark; Islam, Wasif; Richardson, Michelle A.; Parks, Michael L.; Mayman, David J.; MacLean, Catherine H.
Background: Success of treatment for hip or knee osteoarthritis (OA) should be evaluated relative to patients' personal activity goals. Questions/Purposes : We sought to ascertain important principles for collecting such goals and developed a survey informed by those principles to facilitate better shared decision-making. Methods : From a series of 100 patient interviews inquiring about specific activity goals, we identified 6 principles for goal collection that are important to patients and physicians and could practically facilitate better shared decision-making (phase 1). Incorporating these principles, we designed a self-administered survey to measure specific pretreatment activity goals, piloting in 1 surgeon's office (phase 2). During office visits, the feasibility of achieving stated goals was discussed between the surgeon and the patient, and goal modifications were recorded. Results : The phase 2 survey was administered to 252 patients, among whom 130 were women (51.6%); 215 (85.3%), white; mean age, 58.5 years; mean body mass index, 30.2 kg/m 2 ; and 92.9% had 1 or more goals, totaling 106 unique goals. Patient demographics were associated with having goals for walking, running, exercising, golfing, tennis, and stairs. Hip and knee patients could last perform their goal on average 21.7 and 38.6 months prior ( P = .002). Patient and surgeon agreed to modify goals 19% of the time, more often among younger patients ( P = .001) and for running (64% modified, P < .0001) and skiing (42%, P = .0026), but less often for walking (14%, P = .0430) and golf (0%, P = .0204). Conclusions : Patients' activity goals can be captured by a self-administered survey, collected before an office visit, and used to facilitate shared decision-making.